A Qualitative Descriptive Study of Perceived Sexual Effects of Club Drug Use in Gay and Bisexual Men - Palamar, Joseph J. (2012)
Club drug use is often associated with unsafe sexual practices and use remains prevalent among gay and bisexual men. Although epidemiological studies commonly report the risk of engaging in unsafe sex due to the effects of particular club drugs, there remain gaps in the literature regarding the specific sexual effects of such substances and the context for their use in this population. We examined secondary data derived from interviews with 198 club drug using gay and bisexual males in New York City and qualitatively describe subjective sexual effects of five drugs: ecstasy, GHB, ketamine, powder cocaine and methamphetamine. Differences and commonalities across the five drugs were examined. Results suggest that each drug tends to provide: 1) unique sexual effects, 2) its own form of disinhibition, and 3) atypical sexual choices, often described as “lower sexual standards.” Differences across drugs emerged with regard to social, sensual and sexual enhancement, sexual interest, and impotence. Although some common perceived sexual effects exist across drugs, the wide variation in these effects suggests different levels of risk and may further suggest varying motivations for using each substance. This study seeks to educate public health officials regarding the sexual effects of club drug use in this population.